2010
DOI: 10.1016/j.jada.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products in Foods and a Practical Guide to Their Reduction in the Diet

Abstract: Modern diets are largely heat-processed and as a result contain high levels of advanced glycation end products (AGEs). Dietary advanced glycation end products (dAGEs) are known to contribute to increased oxidant stress and inflammation, which are linked to the recent epidemics of diabetes and cardiovascular disease. This report significantly expands the available dAGE database, validates the dAGE testing methodology, compares cooking procedures and inhibitory agents on new dAGE formation, and introduces practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
984
4
58

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,025 publications
(1,068 citation statements)
references
References 43 publications
22
984
4
58
Order By: Relevance
“…Advanced glycation end products (AGEs) are generated from multiple sources and mechanisms (Uribarri et al ., 2010). Chronic accumulation of AGEs is accelerated with aging and with aging‐related diseases such as diabetes, hyperlipidemia, and renal disease (Cho et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) are generated from multiple sources and mechanisms (Uribarri et al ., 2010). Chronic accumulation of AGEs is accelerated with aging and with aging‐related diseases such as diabetes, hyperlipidemia, and renal disease (Cho et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous AGEs, typically encountered in a Western diet, are at least partially absorbed into circulation where they add to the endogenous AGE level [Uribarri et al, 2005; Somoza et al, 2006; Sebekova et al, 2008; Birlouez‐Aragon et al, 2010]. Among the group of AGEs, N‐ϵ‐carboxymethyl‐ l ‐lysine (CML), a well‐characterized, stable [Ahmed et al, 1986; Kislinger et al, 1999; Uribarri et al, 2010] member, and major epitope of AGE‐modified proteins [Ikeda et al, 1996], has been detected in a wide range of foods, its concentration reaching up to 84.8 mg per average portion size in meat dishes [Hull et al, 2012]. In a study on the dose‐dependent utilization of CML in rats, 30% of dietary CML has been shown to enter the blood stream [Somoza et al, 2006].…”
mentioning
confidence: 99%
“…19 The use of vinegar in cooking has been proposed as beneficial in the diet of ESRD patients to decrease potassium and magnesium content of vegetables 22 and to decrease formation of advanced glycation endproducts (AGEs) in foods. 23 This requires reappraisal in light of the current studies. Low protein diets for renal patients will affect the exposure to oxythiamine if they concurrently decrease consumption of cooked thiamine-containing acidic foods.…”
Section: Discussionmentioning
confidence: 91%